2018
DOI: 10.7454/jurnalkessos.v19i2.170
|View full text |Cite
|
Sign up to set email alerts
|

PERAN PENDAMPING DALAM INTERVENSI PADA ORANG DENGAN HIV/AIDS (ODHA) (Studi Deskriptif Pada Kelompok Dukungan Sebaya (KDS) Pelangi Di Klinik Vicity RSUD Balung, Kabupaten Jember)

Abstract: Orang dengan HIV/AIDS (Odha) merupakan salah satu penyandang masalah sosial yang mengalami permasalahan di berbagai dimensi, terlebih pada dimensi sosial seperti terkucilkan dari lingkungan sosial, tidak memiliki dukungan sosial, kesulitan menjalin relasi dengan lingkungan sosial, sehingga menjadi introvert dan tidak percaya diri dengan status dirinya sebagai Odha. Untuk membantu Odha mengatasi masalah pada dimensi sosialnya, di Kabupaten Jember terdapat Kelompok Dukungan Sebaya (KDS) Pelangi yang melakukan in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to [15], peer support for people living with HIV/AIDS is a group consisting of individuals who have similar issues or situations, which serves to provide support to one another. The study conducted by [8] found that peer support involves support given by People Living with HIV/AIDS (PLWHA) to PLWHA, especially those who have recently been diagnosed as HIV positive. Another study by [15] also found that various reasons motivate individuals to become peer supporters for PLWHA, such as personal experiences, a calling to save others after experiencing being an PLWHA themselves, a desire to become a role model for other PLWHA to follow, the need to share experiences, and the desire to help and be beneficial to others.…”
Section: Introductionmentioning
confidence: 99%
“…According to [15], peer support for people living with HIV/AIDS is a group consisting of individuals who have similar issues or situations, which serves to provide support to one another. The study conducted by [8] found that peer support involves support given by People Living with HIV/AIDS (PLWHA) to PLWHA, especially those who have recently been diagnosed as HIV positive. Another study by [15] also found that various reasons motivate individuals to become peer supporters for PLWHA, such as personal experiences, a calling to save others after experiencing being an PLWHA themselves, a desire to become a role model for other PLWHA to follow, the need to share experiences, and the desire to help and be beneficial to others.…”
Section: Introductionmentioning
confidence: 99%